Kewenangan Notaris dalam Membuat Akta Keterangan Waris bagi Para Pihak yang Berdomisili di Luar Tempat Kedudukan Notaris - Mutia Juliantika (Officium Notarium, 2023)
This thesis aims to determine the authority of a Notary in the making of inheritance certificate deeds for parties who live beyond the Notary's place of residence. The problem formulated in this research is first, how to implement Article 111 of the ATR/BPN Ministerial Regulation Number 16 of 2021 on the third amendment to PMNA/Ka BPN Number 3 of 1997 on Provisions for Implementing Government Regulation Number 24 of 1997 on Land Registration, second. What is the authority of a Notary in making an Inheritance Deed after the issuance of ATR/BPN Ministerial Regulation Number 16 of 2021 on the third amendment to PMNA/Ka BPN Number 3 of 1997 on Provisions for Implementing Government Regulation Number 24 of 1997 on Land Registration. The type of this research is normative legal with statutory and conceptual approaches. The results of this research indicate that first, the implementation of changes to Article 111 of the ATR/BPN Ministerial Regulation Number 2021 has had an impact on eliminating discrimination related to making land certificates for Indonesian citizens, and inheritance certificates can be made by Indonesian citizens to a notary in order to apply for inheritance. land certificate at the National Land Agency. Second, the authority of the Notary in making Inheritance Certificate deeds for all Indonesian citizens where the heir passed away at the Notary's place of domicile, the deed made by the Notary is a party deed (partij act) namely a statement of inheritance and an inheritance certificate Deed, has restrictions on the Notary's making the inheritance information, namely the position of a Notary only where the testator passed away, causes a clash of norms with the Notary's authority to make deeds in a provincial area. The government's suggestion is to provide information to the public that notaries can make inheritance certificate deeds for Indonesian citizens and notaries must be careful in making inheritance certificate deeds so that disputes do not occur in the future and the government can make a policy on order for every heir to be able to make inheritance certificate from all Notaries without exception where the domicile of the heir passed away while the authority of the notary is limited within the provinceKey Word: Notary, Authority, Certificate of Heir AbstrakTesis ini bertujuan untuk mengetahui kewenangan Notaris dalam membuat akta keterangan waris bagi para pihak yang berdomilisi di luar tempat kedudukan Notaris. Masalah yang dirumuskan dalam penelitian ini adalah pertama bagaimana Penerapan Pasal 111 Peraturan Menteri ATR/BPN Nomor 16 Tahun 2021 tentang Perubahan ketiga atas PMNA/Ka BPN Nomor 3 Tahun 1997 Tentang Ketentuan Pelaksanaan Peraturan Pemerintah Nomor 24 Tahun 1997 Tentang Pendaftaran Tanah, kedua. Bagaimanakah kewenangan Notaris dalam Membuat Akta keterangan Waris Setelah Terbitnya Peraturan Menteri ATR/BPN Nomor 16 Tahun 2021 tentang Perubahan ketiga atas PMNA/Ka BPN Nomor 3 Tahun 1997 Tentang Ketentuan Pelaksanaan Peraturan Pemerintah Nomor 24 Tahun 1997 Tentang Pendaftaran Tanah. Jenis penelitian ini bersifat hukum Normatif dengan pendekatan perundang-undangan dan pendekatan konseptual. Hasil penelitian ini menunjukkan bahwa pertama, Implementasi telah dirubahnya Pasal 111 Permen ATR/BPN Nomor 2021 berdampak pada penghapusan diskriminasi terkait pembuatan surat keterangan tanah bagi Warga Negara Indonesia, dan surat keterangan Waris dapat dibuat oleh Warga Negara Indonesia pada Notaris dalam rangka untuk permohonan turun waris sertifikat tanah di Badan Pertanahan Nasional. Kedua, kewenangan Notaris dalam membuat akta Keterangan Waris untuk seluruh warga negara Indonesia yang mana pewaris meninggal pada tempat kedudukan Notaris, akta yang dibuat oleh Notaris adalah akta pihak (partij akta) yaitu surat pernyataan Waris dan Akta keterangan waris, hal ini terdapat pembatasan Notaris dalam pembuatan keterangan waris yaitu hanya kedudukan Notaris dimana pewaris meniggal dunia ini menyebabkan benturan norma dengan kewenangan Notaris dalam membuat akta merupakan satu wilayah provinsi. Saran Pemerintah agar dapat melakukan sosialisasi kepada masyarakat bahwa Notaris dapat membuat Akta keterangan waris bagi warga negara Indonesia dan Notaris harus berhati-hati dalam membuat akta keterangan waris agar tidak terjadi sengeketa dikemudian hari dan Pemerintah agar dapat membuat suatu kebijakan agar setiap ahli waris dapat untuk membuat surat keterangan waris di semua Notaris tanpa terkecuali dimana tempat kedudukan pewaris meninggal dunia karena kewenangan notaris merupakan satu wilayah provinsi.Kata-kata Kunci: Notaris, Kewenangan, Surat Keterangan Ahli Waris